Creation of controllable cationic and anionic defects in tunnel manganese oxide nanowires for enhanced oxygen evolution reaction. (1st October 2019) - West, Patrick J.; Byles, Bryan W.; Pomerantseva, Ekaterina
Graphical abstract: Scalable and easy-to-implement approaches, such as acid leaching and transition metal doping, are shown to lead to more than a three-fold increase in activity of low-cost non-toxic manganese oxide electrocatalysts in oxygen evolution reaction to facilitate electrochemical water splitting. Abstract: The development of efficient oxygen evolution reaction (OER) catalysts is crucial to the environmental and economic feasibility of electrolysis for the production of hydrogen gas. In this work, two facile chemical treatments, acid leaching and transition metal doping, were shown to modify the chemical and structural properties of low cost and environmentally friendly α-MnO2 nanowire catalysts resulting in increased OER activity. Through a combination of XPS and XRD analyses, it was shown that a molten salt treatment of α-MnO2 nanowires with Co(NO3 )2 introduced Co 2+ ions into the structural tunnels. The introduction of minimal amounts of cobalt (<6 at. %) more than doubled ultimate current densities achieved in linear sweep voltammetry tests. This result was attributed to a reduction of the average oxidation state of manganese in Co-doped samples and a decrease in Tafel slope below 80 mV·dec −1 . Acid leaching, on the other hand, is believed to modify nanowire topography through the creation of oxygen and manganese vacancies, exposing more active sites to participate in catalysis. A characterization approach combining atomic absorption spectroscopy and iodometric titration revealed a 5.1% increase in oxygen vacancies after 72 h of interaction with nitric acid. When these controllable defect formation approaches were applied in tandem, the high activity of the cobalt-doped samples was combined with the increased number of exposed active sites achieved through acid leaching producing a highly efficient electrocatalyst with more than a 3-fold increase in OER activity over pristine α-MnO2 nanowires. Our results establish that scalable and easy-to-implement approaches, such as acid leaching and transition metal doping, can lead to more than a three-fold increase in OER activity of low-cost non-toxic manganese oxides. This methodology can be beneficial for other material systems used as OER electrocatalysts.